CHOICE OF THE VOLUME OF SURGICAL OPERATION IN ACUTE VARICOTROMBOPHLEBITIS - Juraev O.U.,; Xursanov Y.E., (Research Focus International Scientific Journal, 2024)
In basis research laid down analysis results diagnostics And treatments 102 sick With sharp thrombophlebitis of varicose veins of the lower extremities. Surgical tactics and the choice of the volume of surgery for OVTF depend on from localizations thrombotic process, according to ultrasound Doppler scanning degrees risk thromboembolic complications And duration diseases. Two-stage surgical intervention helps to reduce the risk of developing purulentinflammatory wound complications from 13.9% to 6.3% and the frequency of damage to the subcutaneous nerve from 16.2% to 6.3%, improving the quality of life of patients.